PENERAPAN MODEL DISCOVERY LEARNING DALAM MENINGKATKAN KEMAMPUAN SISWA MENGIDENTIFIKASI STRUKTUR ISI TEKS ANEKDOT DI MAN - Siti Aminah; Sujinah Sujinah (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2026)
ABSTRACT Text-based Indonesian language learning requires students not only to comprehend textual content but also to systematically analyze the structural elements that construct a text. One type of text studied at the Madrasah Aliyah level is the anecdote text, which is characterized by a specific structure consisting of abstraction, orientation, crisis, reaction, and coda. Classroom realities indicate that students still experience difficulties in accurately identifying these structural components. This study aims to examine the effectiveness of implementing the Discovery Learning model in improving students’ ability to identify the structural elements of anecdote texts. This research employed a quantitative approach using a pre-experimental method with a One Group Pretest–Posttest design. The research subjects were tenth-grade students of MAN 1 Merangin. Data were collected through tests measuring students’ ability to identify text structure, classroom observations, and documentation. The Discovery Learning model was implemented through stages of stimulation, problem identification, data collection and processing, verification, and conclusion drawing. The findings reveal a significant improvement in students’ abilities following the implementation of the Discovery Learning model. Both the mean scores and the percentage of learning mastery increased across all structural aspects of anecdote texts. In addition, students demonstrated higher levels of active engagement in text analysis and a deeper understanding of the function of each structural component. Therefore, the Discovery Learning model is proven to be effective and suitable as an alternative instructional approach for text-based Indonesian language learning at the Madrasah Aliyah level. ABSTRAK Pembelajaran Bahasa Indonesia berbasis teks menuntut kemampuan siswa untuk memahami isi sekaligus menganalisis struktur pembangun teks secara sistematis. Salah satu jenis teks yang dipelajari di Madrasah Aliyah adalah teks anekdot yang memiliki struktur khas, meliputi abstrak, orientasi, krisis, reaksi, dan koda. Kenyataan di lapangan menunjukkan bahwa siswa masih mengalami kesulitan dalam mengidentifikasi struktur tersebut secara tepat. Penelitian ini bertujuan untuk mengkaji efektivitas penerapan model Discovery Learning dalam meningkatkan kemampuan siswa mengidentifikasi struktur isi teks anekdot. Penelitian ini menggunakan pendekatan kuantitatif dengan metode pre-eksperimental melalui desain One Group Pretest–Posttest. Subjek penelitian adalah siswa kelas X MAN 1 Merangin. Pengumpulan data dilakukan melalui tes kemampuan identifikasi struktur teks, observasi aktivitas pembelajaran, dan dokumentasi. Model Discovery Learning diterapkan melalui tahapan pemberian rangsangan, identifikasi masalah, pengumpulan dan pengolahan data, verifikasi, serta penarikan simpulan. Hasil penelitian menunjukkan adanya peningkatan kemampuan siswa yang signifikan setelah penerapan model Discovery Learning. Nilai rata-rata dan persentase ketuntasan belajar siswa mengalami peningkatan pada seluruh aspek struktur teks anekdot. Selain itu, siswa menunjukkan keterlibatan yang lebih aktif dalam menganalisis teks dan memahami fungsi setiap bagian struktur secara mendalam. Dengan demikian, model Discovery Learning terbukti efektif dan layak digunakan sebagai alternatif pembelajaran Bahasa Indonesia berbasis teks di Madrasah Aliyah.